Effect of Role School Committee and School Operational Fund on Quality of Education - Efendi, Rusdi; Fitria, Happy; Nurkhalis, Nurkhalis (Yayasan Sembilan Pemuda Indonesia, 2020)
This study determined whether there is any influence and how much influence the role of the school committee and school operational assistance programs on the quality of education. This research was conducted in SMP Negeri Rambang, Muara Enim. This type of research is quantitative research. While the method in this research uses the partial correlation method. The sample in this study were 45 educators and teaching staff at the school. The data collection technique in this study used a questionnaire. The results of this study showed that 1) there is a relationship between the role of the school committee and the school operational assistance program; 2) there is an influence between the role of the school committee on the quality of education; 3) there is an influence between the school operational assistance program on the implementation of education quality; and 4) there is a significant joint effect between the role of the school committee and the school operational assistance program on the quality of education.